Population background exploration and genetic distribution analysis of Pakistan Hazara via 23 autosomal STRs - Pengyu Chen; Atif Adnan; Allah Rakha; Mengge Wang; Xing Zou; Xiaodan Mo; Guanglin He (Taylor & Francis Group, 2019)
Background: Short tandem repeats (STRs) have gained considerable attention in family search (Y-chromosomal STRs), complex paternity identification (X-chromosomal STRs), routine forensic personal identification (autosomal STRs) and population genetics. Aim: To explore the forensic characteristics of 23 autosomal STRs included in the Huaxia Platinum system in the South Pakistan Hazara population and investigate the genetic similarities and differences between Hazara and 54 worldwide reference populations. Subjects and methods: Variation of the 23 autosomal STRs included in the Huaxia Platinum system was first investigated and reported in a sample of 261 Quetta Hazara in Balochistan Province, Southwest Pakistan. Results: The combined power of discrimination is 0.999999999999999999999999999 and combined power of exclusion is 0.99999999989596 in Quetta Hazara. Comprehensive population comparisons between Hazara and another 13 Eurasian populations based on genotype data, as well as between Hazara and 54 worldwide populations based on the allele frequency distribution, were conducted. Multidimensional scaling plots, principal component analysis, and neighbour-joining phylogenetic trees consistently demonstrated that Pakistan Hazara harbours close affinities with neighbouring Turkic-speaking populations. Model-based genetic structure analysis further suggests that Quetta Hazara derives about half its ancestry directly from the East Asians. Conclusion: Twenty-five forensic-related markers included in the Huaxia Platinum system can be used for forensic practice in the Central Asia Hazara population. Quetta Hazara has a close genetic relationship with the Turkic-speaking populations of Uyghur and Kazakh. Further whole-genome sequencing of Hazara needs to be conducted to validate the observed genetic structure and reconstruct the fine-scale population history of Hazara.